PENGARUH LATIHAN PLIOMETRIK BARRIER HOPS DENGAN LATIHAN KOMANDO TERHADAP PENINGKATAN PRESTASI SHOOTING SSB INDONESIA MUDA KOTA MALANG - Wahyudi Wahyudi; Hariyoko Hariyoko; Fahrial Amiq (Jurnal Pendidikan Jasmani)
Abstract: Research aims to understand the influence of exercise pliometrik barrier hops on increased shooting school student achievement football Indonesia Muda Kota Malang. Research used is experiment conducted to students school football Indonesia Muda Kota Malang by the span of aged 13-15 were 30 students. Based on the results of the testing of hypotheses test t amatan ulang each group exercise obtained t count of 66,910 > t table 2,145 for the exercise barrier hops and training command obtained t count of 4,848 > t table 2,145. So that it can be concluded that is the significant between a pre-test by a test the end of achievement a shot inside the post (shooting) from each group exercise.Key words: Pliometrik, exercise command, a shot inside the post (shooting)